Features the elevation of the outer rail in the curved part of the road (Международный научный журнал «Инженер», 2026)
In the layout of a railway track, its curved section is of particular importance. When transitioning from onestraight section of the track to another, a curved segment arises. In the curved section, the outer rail is elevatedto neutralize the centrifugal force that appears during the turning of the train. This study is dedicated toanalysing the functional properties of the elevation of the outer rail in a railway track. The transition sectionis divided into two equal parts. This division becomes the centre of symmetry for both parts. Such aconfiguration ensures a smooth and symmetric transition of the train at both ends of the transitional section.The elevation function value is calculated using a differential equation derived by the author. The layout ofthe elevated part is presented in a schematic drawing, and a method is proposed to compute the elevation thatensures a smooth transition of the train from a straight section to a curved one.